Flood Points Distribution Mapping for the Determination of Evacuation Routes and Disaster Posts in Gorontalo City. Issue 1 (November 2020) - Indrawan,; Yusuf, Daud
Abstract: This research used Geographic Information System (GIS) approach with Round Graph method. Data used in this research are high resolution satellite imagery, Peta Rupa Bumi Indonesia (RBI) scale 1: 25.000 and Statistics data. High resolution satellite imagery was used to obtain data about the distribution of flood points, road map and locations of disaster posts. After obtaining those data, then the quickest and nearest evacuation routes can be determined by using round graph method so that the casualty of flood hazard can be significantly reduced and effectively helped.